Phytochromes from Agrobacterium fabrum1. (May 2017) - Lamparter, Tilman; Krauß, Norbert; Scheerer, Patrick
Abstract: Agrobacterium fabrum is a widely used model bacterium for gene transfer from pro‐ to eukaryote, for genetics and metabolism. The phytochrome system of Agrobacterium, encompassing the two phytochromes Agp1 and Agp2, has provided deep insight into phytochrome action in a bacterial organism. This review summarizes recent results on phytochrome evolution, phytochrome regulation of conjugation and plant infection and biochemical studies including the crystal structure of Agp1‐PCM, the photosensory core module of Agp1. Abstract : Phylogenetic tree based on the photosensory core modules (PCMs) of bacterial (blue), cyanobacterial (cyan), plant (green), fungal (orange) and diatom (magenta) phytochromes. The groups to which Agrobacterium phytochromes Agp1 and Agp2 belong are indicated. The superposed structures are from PCMs of Agp1 (orange) from Agrobacterium fabrum, a surface‐engineered mutant of Agp1 (blue) and of the bathy phytochrome PaBphP (black) from Pseudomonas aeruginosa . The long helix that connects the GAF and PHY domains of phytochromes shows the different degrees of bending. Photoconversion from Pr to Pfr results in a straightening of this helix.